Object and Apparition : Envisioning the Christian Divine in the Colonial Andes - Stanfield-Mazzi, Maya Selama, 1972- (Book collections on Project MUSE., 2013)
Based on archival research combined with visual analysis, the author demonstrates that Andeans were active agents in Catholic image-making and created a particularly Andean version of Catholicism. This book describes the unique features of Andean Catholicism while illustrating its connections to both Spanish and Andean cultural traditions.--description provided by publisher.